Oriental Republic of Uruguay : Integration into Global Value Chains the Dairy Industry and the ICT Industry - Criscuolo, Alberto; Onugha, Ifeyinwa Uchenna; Varela, Gonzalo (World Bank, Buenos Aires, 2018)
Uruguay has much to gain from further integration with the global marketplace. Increased trade allows economies of scale and increases exposure to technological and knowledge spillovers, resulting in greater productivity. Participating in global and regional value chains is an important launch-pad for international integration. Uruguay requires a multipronged strategy that targets increased sophistication of Uruguay’s productive structure and diversification into specialized, high-value, modern services exports unconstrained by lack of economies of scale or distance. This report analyzes the dairy and Information & Communications Technology (ICT) and ICT Enabled Services (ICTES) value chains in Uruguay to identify opportunities for industry-specificupgrading and integration with global value chains (GVCs). By taking the dairy and ICT/ICTES value chains as concrete cases, the analysis piloted here illustrates how a traditional industry, locked in low value added exports, such as dairy, and a new export service industry, such as ICT/ICTES, can tackle the remoteness and ‘smallness’ challenges of Uruguay, and pursue economic upgrading andbetter international integration. The analytical approach targets opportunities to both enter new international production networks and participate in higher-value-added business segments. These objectives align with the Government of Uruguay’s priority to determine how the country can integrate better with global markets through GVCs. GVCs have four key features that set them apart from traditional production and trade: (1) customization of production—with intensive contracting between parties, often subject to distinct legal systems, (2) sequential production decisions going from the buyer to the suppliers, (3) high contracting costs, and (4) global matching not onlyof goods and services, but also of production teams. These distinct features of GVCs have implications for the overall business environment conducive to fertile grounds for GVCs to prosper, as well as for the types of trade facilitation efforts, infrastructure, skills, and trade and investment policies that are best suited for this reality.